Nitrate in groundwater of the Jurassic aquifer in Olkusz region (southern Poland) - ŻUREK, Anna; CZOP, Mariusz; MOTYKA, Jacek (Geology, Geophysics and Environment, 2010)
Jurassic aquifer represents the Major Groundwater Basin (MGWB) 326 which is located in Upper Jurassic carbonate rocks. The hydrodynamic conditions in the Jurassic aquifer are very complex, with different types of hydraulic connections with neighbouring aquifers. Therefore the quality of the Jurassic aquifer has affected groundwater quality in Quaternary and Triassic rocks. Nitrates have been the main indicator of groundwater contamination. The regime of springs located in the study area (high fluctuation of discharge and temperature) indicates local drainage. The quality of spring-water has reflected the land use of spring recharge area. The chemistry of deep well-water has shown the quality variation of regional flow system water. Nitrate variability in spring-water (period 2001-2008) and in well-water (1995-2007) has indicated the regional trends of groundwater quality changes in the Jurassic aquifer near Olkusz.